Cigarillo and multiple tobacco product use and nicotine dependence in adolescents and young adults. (December 2020) - Ishler, Karen J.; Flocke, Susan A.; Albert, Elizabeth L.; Trapl, Erika; Gunzler, Douglas
Highlights: Cross-sectional web survey of 1089 adolescent and young adult cigarillo users. 7 distinct tobacco product use patterns identified using latent class analysis. 5 of 7 patterns characterized by use of multiple tobacco products. Multi-product use tied to higher nicotine dependence, especially if cigarettes used. Abstract: Introduction: Multiple tobacco product (MTP) use is a growing public health concern, particularly among adolescents and young adults. This study identifies subgroups of MTP use among cigarillo users and examines associations with nicotine dependence (ND). Methods: 1089 youth (ages 14–28) who currently smoke cigarillos completed a web-based survey regarding their current use of cigarillos, little cigars, traditional cigars, cigarettes, e-cigarettes, and waterpipe/hookah. Latent class analysis (LCA) was used to identify patterns of product use by type and amount. The LCA also assessed the relationship between the latent classes and a 38-item measure of ND, controlling for relevant demographics. Results: Most participants (88.2%) reported using two or more tobacco products in the past 30 days. The best-fitting LCA solution revealed 7 classes: (1) Mixed-Light tipped cigarillo and light cigarette users, 28.9%; (2) Light tipped cigarillo users, 15.8%; (3) Light untipped cigarillo users, 14.3%; (4) Heavy tipped cigarillo users, 13.4%; (5) E-cigarette and waterpipe users, 11.9%; (6) Heavy users of tipped and untipped cigarillos and light users of cigarettes, 9.8%; and (7) Dabblers who primarily used traditional cigars, but were also likely to use a variety of other products, 6.1%. Classes comprised of those using multiple products—particularly those that included cigarettes—had significantly higher levels of ND than other classes (Tukey's HSD P < .05). Conclusions: Distinct patterns of MTP use are evident among young cigarillo smokers. Smoking multiple products, particularly smoking cigarillos in combination with cigarettes, is associated with higher ND compared to other product use patterns.